2019
DOI: 10.1002/jper.19-0390
|View full text |Cite
|
Sign up to set email alerts
|

Using periodontal staging and grading system as a prognostic factor for future tooth loss: A long‐term retrospective study

Abstract: Background: A new classification of periodontal diseases aimed to identify periodontal disease based on a multidimensional staging and grading system has been recently proposed. However, up to date, its prognostic predictive capability has not been investigated. The aim of this study was to assess if parameters included in the new classification were predictive of tooth loss after a long-term follow-up (>10 years) in patients with periodontitis. Methods: Patients presented with periodontitis at the University … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
52
2
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 26 publications
4
52
2
3
Order By: Relevance
“…Patients are further classified into three grades (A, B, C), determined by the past disease progression (measured via the bone loss/age index) and further factors (Tonetti et al., 2018). Such classification has been shown to be able to reflect the disease characteristics, but also tooth loss (Graetz et al., 2019; Ravida et al., 2019). It remains unclear how the severity and extent of the initial diagnoses according to this classification can be associated with long‐term OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…Patients are further classified into three grades (A, B, C), determined by the past disease progression (measured via the bone loss/age index) and further factors (Tonetti et al., 2018). Such classification has been shown to be able to reflect the disease characteristics, but also tooth loss (Graetz et al., 2019; Ravida et al., 2019). It remains unclear how the severity and extent of the initial diagnoses according to this classification can be associated with long‐term OHRQoL.…”
Section: Introductionmentioning
confidence: 99%
“…In one of the main articles of the new classification, Papapanou and coworkers suggested using existing databases as well as developing new databases in order to facilitate the implementation, validation and continuous refinement of the new classification system (Papapanou et al, 2018). In a previous article from our group, we investigated staging, grading and extent as independent variables in a compliant cohort of 292 patients and we found that staging and grading at baseline were significantly associated with risk for tooth loss due to periodontitis (TLP; Ravida et al, 2020). However, the sample size was not large enough to allow for powerful analysis of two-way interactions between prognostic variables.…”
mentioning
confidence: 99%
“…Therefore, stage I or II periodontitis not only differ from staged III or IV periodontitis in terms of disease severity but also show different disease trajectories. Thus, those who present with stage III or IV periodontitis are likely to respond unpredictably to standard periodontal therapy, which focuses on reducing the bacterial burden in gingival crevices 20 .…”
Section: Discussionmentioning
confidence: 99%